Identification of vulnerable areas to floods in kelantan river sub- basins by using flood vulnerability index - Ibrahim, Nurul Farahen (Geotec., Const. Mat. & Env, 2017)
Flood vulnerability indices for the Kelantan River sub-basins were developed from various floodrelated variables. The vulnerability indices of the Ke lantan River sub-basins involved flood depth-inundation area, soil erosion potential, and potential of soil for agricultural use, population vulnerability, road infrastructure vulnerability and market infrastructure vulnerability. These indices were developed from the use of Geographic Information System (GIS) technique. The result indicates that the flood vulnerability indices of sub-basins were mostly ranked high in the areas with high concentration of development activities and densely populated region with large infrastructure exis tence that are more flood-prone group than others especially in major metropolitan areas. In order to steer against probable damage caused by flood, it remains important to develop a t ool that is most beneficial for river basin managers and policy makers, so that they can conduct vulner ability assessment and flood risk in term of human lives losses and property damages during future ma ssive floods. The output of this study can guide decision makers to reduce flood risks Kelantan River basin in future.